2023
DOI: 10.3389/fimmu.2023.1188079
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane product, endostatin, as a link between inflammation, coagulation and vascular permeability in COVID-19 and non-COVID-19 acute respiratory distress syndrome

Abstract: BackgroundImmune cell recruitment, endothelial cell barrier disruption, and platelet activation are hallmarks of lung injuries caused by COVID-19 or other insults which can result in acute respiratory distress syndrome (ARDS). Basement membrane (BM) disruption is commonly observed in ARDS, however, the role of newly generated bioactive BM fragments is mostly unknown. Here, we investigate the role of endostatin, a fragment of the BM protein collagen XVIIIα1, on ARDS associated cellular functions such as neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…W. Kübler (Berlin, Germany) presented advances in the understanding of tissue barrier dysfunction in pathogen-associated respiratory failure. It has been found that the matrikine endostatin is increased in the lungs of patients with acute respiratory distress syndrome (ARDS), including COVID-19-related ARDS, and this increase promotes thrombin-induced epithelial barrier dysfunction and platelet and neutrophil activation [ 45 ]. Loss of the endothelial aryl hydrocarbon receptor (AHR) also increases tissue barrier dysfunction and subsequent movement of inflammatory cells into alveoli following influenza infection.…”
Section: Scientific Year In Reviewmentioning
confidence: 99%
“…W. Kübler (Berlin, Germany) presented advances in the understanding of tissue barrier dysfunction in pathogen-associated respiratory failure. It has been found that the matrikine endostatin is increased in the lungs of patients with acute respiratory distress syndrome (ARDS), including COVID-19-related ARDS, and this increase promotes thrombin-induced epithelial barrier dysfunction and platelet and neutrophil activation [ 45 ]. Loss of the endothelial aryl hydrocarbon receptor (AHR) also increases tissue barrier dysfunction and subsequent movement of inflammatory cells into alveoli following influenza infection.…”
Section: Scientific Year In Reviewmentioning
confidence: 99%